Penggunaan Aplikasi Quizizz Sebagai Media Evaluasi Pembelajaran PAI Berbasis Teknologi Pendidikan Di SMA Negeri 1 Tebing Tinggi Kab. Serdang Bedagai - Kartika, Lesti; Novianti, Winda; Khairun Nizar, Muhammad Alang (At-Tarbiyah: Journal of Islamic Religious Research and Education, 2024)
This study aims to analyze the use of the Quizizz application as a technology-based evaluation tool for Islamic Religious Education (PAI) at SMA Negeri 1 Tebing Tinggi, Serdang Bedagai Regency. This research employs a case study approach to explore three main aspects: planning, implementation, and evaluation outcomes of using the Quizizz application in the learning process. The results indicate that the planning for Quizizz use was carried out systematically, with thorough preparation concerning both content and infrastructure. The implementation of the application in the learning process successfully increased student engagement and provided real-time feedback to teachers. The evaluation outcomes showed a significant improvement in students' understanding of the PAI material, as well as positive responses from students regarding the use of the application. This study contributes to the development of technology-based evaluation methods in Islamic education and offers guidance for educators in optimizing the use of technology in the learning process.